Half a king - Abercrombie, Joe (Abercrombie, Joe. Shattered sea, 2014)
Heir to the throne Yarvi, prompted by the murder of his father, embarks on a kingdom-transforming journey to regain the throne, even though having only one good hand means he cannot wield a weapon.